대추 물 추출물이 RANKL에 의해 유도되는 파골세포 분화에 미치는 영향 - 윤강휴(Yoon Kang Hugh); 백종민(Jong Min Baek); 김주영(Ju Young Kim); 곽성철(Seong Cheoul Kwak); 천윤희(Yoon Hee Cheon); 전병훈(Byung Hoon Jeon); 이창훈(Chang Hoon Lee); 최민규(Min Kyu Choi); 오재민(Jaemin Oh); 이명수(Myeung Su Lee); 김정중(Jeong Joong Kim) (동의생리병리학회지, 2014)
Bone homeostasis is maintained by balance between bone resorbing-osteoclasts and bone forming-osteoblasts. Excessive osteoclastic bone resorption plays a critical role in bone destruction in pathological bone diseases such as osteoporosis, rheumatoid arthritis, and periodontal disease. Many compounds derived from natural products have pharmacological applications and have therapeutic value for treating or preventing several bone diseases characterized by excessive bone resorption. To discover new compounds that can act as anti-resorptive agents, we screened for natural compounds that regulate osteclast differentiation, and found that water extract of Ziziphus Jujuba Mill (WEZJ) has inhibitory effects on osteoclast differentiation. In this study, WEZJ clearly inhibits the osteoclast differentiation in the presence of receptor activator of nuclear factor kB (RANKL), macrophage colony-stimulating factor (M-CSF) without cytoxicity by blocking activation of nuclear factor of activated T cells (NFAT)c1, and c-Fos. In signaling pathway, the phosphorylation of Akt, p38, c-Jun N-terminal kinases (JNK), extracellular signal-regulated kinases (ERK) and the expression of osteoclast-associated receptor (OSCAR), tartrate-resistant acid phosphates (TRAP), Integrin av, Integrin b3, Cathepsin K are suppressed, too. These result suggest that WEZJ may have therapeutic value for treating or preventing several bone diseases characterized by excessive bone destruction.